Avaliação do efeito da sertralina sobre os tecidos periodontais de ratos Wistar com periodontite induzida - Correia, Bruna Rafaela (2021)
Evidence indicates that oral health is directly associated with systemic diseases, in the oral cavity there is the presence of several microorganisms, which can trigger Periodontal Disease (PD), with this, in depression, numerous antidepressant drugs are administered, among them, the sertraline drug , selective serotonin uptake inhibitor (SSRI). This is a neurotransmitter that promotes an increase in its concentration in the bloodstream, significantly decreasing the effects caused by this disease. A study aims to evaluate the effects of sertraline in periodontal tissues with rats induced to ligation periodontitis. 40 adult male rats were used, divided into 4 groups, control group (CG); group with periodontal disease, (GDP); sertraline group (GS); sertraline group with periodontal disease (GSDP). The groups with periodontal disease received a ligature around the first molars for a period of 30 days, and experimentally induced periodontitis developed. The disease was induced with the animals anesthetized, intraperitoneally, with ketamine hydrochloride and xylazine hydrochloride. With the aid of a modified tweezers and an explorer probe, a cotton thread number 40 was added around the lower first molar on both sides, the animals presented food restriction of 8 hours before the procedure of induction of periodontitis. In the animals of the sertraline groups, doses of 5 mg / kg of body weight were administered on alternate days, diluted in 0.9% saline solution, administered orally in a volume of 1mL / 100g of weight. Control animals received 1 mL / kg of weight of 0.9% saline to induce the same stress between groups. After the 60-day experimental period, the animals were anesthetized and beheaded with guillotine and the hemi-mandibles were dissected, which were subjected to morphological and radiographic analysis (containing osteoblasts, osteocytes and osteoclasts). These results were displayed in spreadsheets and analyzed by the GraphPad Program, the data presented through means and a value of p <0.05 will be considered statistically significant. The normalities of the described data, with ANOVA test, indicated parametric and nonparametric results. The results show that there were no statistical differences in terms of feed efficiency, kidney and liver weight, however, the radiographic and histometric analyzes of the hemi-mandibles showed that the GC and GS groups are similar and the GDP and GDPS are similar. statistically similar to the Tukey test, however the groups that did not receive the experimental periodontitis by ligation, showed statistically less alveolar bone loss compared to the other groups (p <0.05). Thus, sertraline had no effect on the periodontal tissues of rats with ligature-induced periodontitis.